2002
DOI: 10.1002/jtr.361
|View full text |Cite
|
Sign up to set email alerts
|

Tourism occupations and education: an exploration study

Abstract: This article contributes to the literature on the relationship between the tourism industry and vocational tourism education. It reports on an exploratory study of the work of a sample of tourism professionals and their education. The study attempts to classify tourism occupations by modifying an established scheme used in general administration. The study sought to ®nd commonality within the diverse occupations and to go on to relate that to tourism education. The study found that the majority of the sample o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 12 publications
(10 reference statements)
0
16
0
Order By: Relevance
“…The concept of competence is either implicitly or explicitly addressed in the publications of tourism education (e.g. Airey & Johnson, 1999;Baum, 2002;Busby, 2001Busby, , 2003Christou, 2000;Churchward & Riley, 2002;Gunn, 1998;Jafari, 1990;Koh, 1995;Munar & Montañ o, 2009;Tribe, 1996;Watson & McCracken, 2002). As Munar (2007) suggests, the use of competences as a common standard to describe courses and educational activities is one of the pieces of a complex puzzle of initiatives that aim to achieve the establishment of a common European higher education area (EHEA).…”
Section: Introductionmentioning
confidence: 98%
“…The concept of competence is either implicitly or explicitly addressed in the publications of tourism education (e.g. Airey & Johnson, 1999;Baum, 2002;Busby, 2001Busby, , 2003Christou, 2000;Churchward & Riley, 2002;Gunn, 1998;Jafari, 1990;Koh, 1995;Munar & Montañ o, 2009;Tribe, 1996;Watson & McCracken, 2002). As Munar (2007) suggests, the use of competences as a common standard to describe courses and educational activities is one of the pieces of a complex puzzle of initiatives that aim to achieve the establishment of a common European higher education area (EHEA).…”
Section: Introductionmentioning
confidence: 98%
“…General Managers, conversely, consider listening as their key competence.Competency research has also been studied in various hospitality sectors with focus on recruitment from educational programs(Chung-Herrara, Enz, & Lankau, 2003, Churchward & Riley, 2002, Tesone & Ricci, 2005.…”
mentioning
confidence: 99%
“…Koh (1994) pursued the curricula issues from a US perspective and by drawing on earlier research (Golden, 1992;Ketyer, 1982;Knutson, 1989) indicated that most of the tourism curricula were "designed by educators (influenced by their individual biases) with little/no representation from the tourism industry." Churchward and Riley (2002) examined the generic content of jobs and the relationship of tourism education to job content. This is aligned to the study in this paper in that as Churchward and Riley Education, ATTHE).…”
mentioning
confidence: 99%